2014
DOI: 10.1021/ac5015518
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Analysis of 22 Volatile Organic Compounds in Cigarette Smoke Using Gas Sampling Bags for High-Throughput Solid-Phase Microextraction

Abstract: Quantifying volatile organic compounds (VOCs) in cigarette smoke is necessary to establish smoke-related exposure estimates and evaluate emerging products and potential reduced-exposure products. In response to this need, we developed an automated, multi-VOC quantification method for machine-generated, mainstream cigarette smoke using solidphase microextraction gas chromatography–mass spectrometry (SPME-GC–MS). This method was developed to simultaneously quantify a broad range of smoke VOCs (i.e., carbonyls an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
49
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 26 publications
5
49
1
Order By: Relevance
“…Cigarette tobacco smoke BTEXS and 2,5-dimethylfuran levels used in this study were quantified using Tedlar bag collection of machine smoked cigarettes followed by equilibrium headspace SPME/GC/MS analysis as described elsewhere (Sampson et al 2014). These cigarette smoke VOC levels were generated using the ISO (3308:2012) and Canadian Intense (CI) protocols from 50 U.S. brand varieties of cigarettes from brand families that comprise 78% of the market share at the time of the sampling (Pazo et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Cigarette tobacco smoke BTEXS and 2,5-dimethylfuran levels used in this study were quantified using Tedlar bag collection of machine smoked cigarettes followed by equilibrium headspace SPME/GC/MS analysis as described elsewhere (Sampson et al 2014). These cigarette smoke VOC levels were generated using the ISO (3308:2012) and Canadian Intense (CI) protocols from 50 U.S. brand varieties of cigarettes from brand families that comprise 78% of the market share at the time of the sampling (Pazo et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Up to now, the major trapping methods of furan in vapor phase of mainstream cigarette smoke were direct injection method (Hatzinikolaou et al 2006, Grob et al 1965, Vickroy et al 1976) and gas bag trapping method (Sampson et al 2014). Grob et al (1965) reported on determination of furan in cigarette smoke directly through a gas sampling valve by gas chromatography (GC) coupled with flame ionization detector (FID) without sample collection.…”
mentioning
confidence: 99%
“…However, soft photoionization and puff-by-puff analysis were adopted in their reports, which made these methods complicated and difficult to operate. Sampson et al (2014) reported a method that the vapor phase of mainstream cigarette smoke was collected by a gas bag, and furan was detected by solidphase microextraction gas chromatography -mass spectrometry (SPME-GC-MS). And the emissions of furan in the research cigarettes (1R5F and 3R4F) under ISO and CI smoking regimens were reported.…”
mentioning
confidence: 99%
See 2 more Smart Citations